Eight new species of Costanana DeLong & Freytag (Hemiptera: Cicadellidae: Gyponini): taxonomic changes, key to males, and description of Metacostana gen. nov. - Domahovski, Alexandre C.; Cavichioli, Rodney R. (European Journal of Taxonomy, 2023)
Costanana DeLong & Freytag, 1972 is a Neotropical genus of leafhoppers currently comprising 13 species with a wide distribution from Mexico to Argentina. In this study, eight new species of Costanana are described, C. xenomorpha sp. nov. from Department of Cuzco, Peru, and seven Brazilian species: C. alata sp. nov. from Minas Gerais State; C. bifida sp. nov. from Paraná and Mato Grosso states; C. cifi sp. nov., C. obtusa sp. nov. and C. piraquarensis from Paraná State; C. luzi sp. nov. from Distrito Federal; and C. rubromarginata sp. nov. from Mato Grosso and Pará states. We propose that Costanana cella DeLong & Freytag, 1972 is a junior synonym of C. praecellens (Stål, 1862) and C. asymmetrica DeLong & Freytag, 1972 is a junior synonym of Gypona viridans DeLong & Martinson, 1972. Costanana costata DeLong & Freytag, 1972 and C. flavicosta (Stål, 1862) are transferred to Gypona Germar, 1821, C. minuta (Spångberg, 1878) is transferred to Acuponana DeLong & Freytag, 1970 and Gypona nupera Van Duzee, 1907 is transferred to Costanana. Gypona costata comb. nov. and Costanana santana DeLong & Wolda, 1983 are newly recorded from Pernambuco State, and Gypona flavicosta comb. nov. is recorded from Espírito Santo and Paraná states, Brazil. The female genitalia of Costanana flavina DeLong & Freytag, 1972, C. praecellens and Gypona flavicosta comb. nov. are described and illustrated for the first time and a brief note on feeding behavior is given for C. flavina and C. praecellens. A key to males and a new diagnosis are provided for Costanana. We also describe and illustrate Metacostana cornuta gen. et sp. nov., a new Brazilian genus for Gyponini sharing characteristics with Costanana, Acuthana Domahovski & Cavichioli, 2018, Domahovana Silva et al., 2022 and Dumorpha DeLong & Freytag, 1975.